Gene‐edited or genetically modified food? The impacts of risk and ambiguity on Chinese consumers' willingness to pay. (22nd February 2023) - Ding, Yulian; Yu, Jianyu; Sun, Yangyang; Nayga, Rodolfo M.; Liu, Yunyun
Abstract: This study investigates consumer preferences for newly introduced gene‐edited (GE) food. We focus on how risk and ambiguity aversion affect consumers' willingness to pay (WTP) to avoid genetically modified (GM) food or GE food and whether the impacts of risk and ambiguity aversion differ between GM and GE food. We collected the data in 2020 through a nationwide online survey in China. The multiple price list method is used to estimate the premiums that consumers are willing to pay for conventional rice to avoid GM/GE rice. Our results show that Chinese urban consumers are more concerned about the health, environmental, and ethical impacts of genetic modification than gene editing technology. They are willing to pay lower premiums when the alternative is GE rice than when it is GM rice. We further find that both risk aversion and ambiguity aversion have significant negative impacts on respondents' WTP for food derived from gene technologies, with ambiguity aversion being more influential than risk aversion for both GM and GE rice. However, there is no significant difference in how risk aversion and ambiguity aversion affect the respondents' WTP to avoid GM or GE rice.